Deontic modality and the category of performativity in the aspect of legal text's linguistics - Skorofatova, Аnna (Current issues of Ukrainian linguistics: theory and practice, 2024)
The article states that the problem of verbal expression of performativity in a legal text is debatable, therefore, the author considers language and non-language marks of the executive power of the legislator's statements in the form of legal prescriptions; characterizes means of expression of deontic modality in normative legal acts; determines the language components of the performativity of the act of establishing the law by means of a pragmatic analysis of a legal text; describes categorical properties of a legal expression; analyses textual and non-textual marks of performativity in the context of deontic modality and directiveness of normative utterances. Among the means of expressing deontic modality in legal texts, a precept, prohibition and permission in explicit and implicit expression are considered on the examples of legal acts, in particular the Criminal Code of Ukraine. Performatives against the background of other speech acts are typologically divided into verdictives (judgments, decrees, sentences), commissives (obligations, promises, declared intentions), behavitives (behaviour in society – greetings, apologizing, condoling, etc.), expositives (metalanguage statements), exercitives (utterances that exercise powers). The research made it possible to establish that legal texts as units of legal discourse are performative in terms of their language and non-language marks. The legal prescriptions that contained in them are established in a traditional manner and are obligatory. The system of these prescriptions exists in the public consciousness and creates legal relations. The article presents only some logical and linguistic characteristics of deontic modality and performativity of legal texts, therefore, numerous aspects of other categories of legal texts (communicativeness, coherence and intertextuality) require further development.
Keywords: deontic modality, performative, performative utterance, normative utterance, legal text, modus, dictum, textual and extratextual performativity.